Modelling Overcurrent Protection Relay Using PSCAD at Pencawang Masuk Utama Jasin - Hairi, M. H.; Mohd Isira, A. S.; Kamarudin, M. N.; Packeer Mohamed, M. F.; Sobri, S. A. (International Journal of Electrical Engineering and Applied Sciences (IJEEAS), 2025)
This paper focuses on modelling 132/11kV Pencawang Masuk Utama (PMU) Jasin, Melaka for assessing the Inverse Definite Minimum Time (IDMT) overcurrent relay in terms of relay response time using PSCAD software. The relay is subjected to various fault conditions such as three phase fault, double phase, and single-phase fault at different point of the network to observe the operating time. To ensure the reliability of the overcurrent relay, the response time has been analysed. The response time were then being verified accordingly and the result shows that relay response time were successfully simulated.